ОЦЕНКА СТАТУСА ПИТАНИЯ СПОРТСМЕНОВ ПО БИОХИМИЧЕСКИМ ПОКАЗАТЕЛЯМ (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2024)
In martial arts athletes, changes in the qualitative composition of diets made it possible to normalize the biochemical parameters of nitrogenous components of urine in athletes, improve protein digestibility and normalize mg/hour excretion of vitamin C. The best indicators characterizing the state of protein and vitamin metabolism were obtained from the study subjects who, in addition to the modified diet, received dietary supplements “Kuvatin”, “Bioferron” and 2 liters of artificially mineralized water “Bonaqua” per day.